Liver X Receptor as a Possible Drug Target for Blood-Brain Barrier Integrity - Mahsa Eskandari; Ali Awsat Mellati (Tabriz University of Medical Sciences, 2022)
Purpose: blood-brain barrier (BBB) is made of specialized cells that are responsible for theselective passage of substances directed to the brain. The integrated BBB is essential for precisecontrolling of the different substances passage as well as protecting the brain from variousdamages. In this article, we attempted to explain the role of liver X receptor (LXR) in maintainingBBB integrity as a possible drug target.Methods: In this study, various databases, including PubMed, Google Scholar, and Scopus weresearched using the following keywords: blood-brain barrier, BBB, liver X receptor, and LXR untilJuly, 2020. Additionally, contents close to the subject of our study were surveyed.Results: LXR is a receptor the roles of which in various diseases have been investigated. LXRcan affect maintaining BBB by affecting various ways such as ATP-binding cassette transporterA1 (ABCA1), matrix metalloproteinase-9 (MMP9), insulin-like growth factor 1 (IGF1), nuclearfactor-kappa B (NF-κB) signaling, mitogen-activated protein kinase (MAPK), tight junctionmolecules, both signal transducer and activator of transcription 1 (STAT1), Wnt/β-cateninSignaling, transforming growth factor beta (TGF-β) signaling, and expressions of Smad 2/3 andSnail.Conclusion: LXR could possibly be used either as a target for drug delivery to brain tissue or as atarget for maintaining the BBB integrity in different diseases; thereby the drug will be conductedto tissues, other than the brain. If it is verified that only LXRα is necessary for protecting BBB,some specific LXRα ligands must be found and then used in medication.